2006
DOI: 10.1590/s0101-81752006000100019
|View full text |Cite
|
Sign up to set email alerts
|

Diet of the fishing bat Noctilio leporinus (Linnaeus) (Mammalia, Chiroptera) in a mangrove area of southern Brazil

Abstract: From January to December 1999, the diet of Noctilio leporinus (Linnaeus, 1758) was determined in a salt-water ecosystem, by analysing the feces of bats captured in mist nets. Of the 61 samples analyzed, most contained remains of fish (90.2%), followed by insects (70.5%) and crustaceous (29.5%). The most frequent fishes species were: silversides Atherinella brasiliensis (Quoy & Gaimard, 1825), anchovies Cetengraulis edentulus (Cuvier, 1829) and scaly sardines Ophisthonema oglinum (Lesueur, 1818). The most f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 23 publications
0
24
0
4
Order By: Relevance
“…For example, Noctilio leporinus (Linnaeus, 1758) is often strongly infested by Noctiliostrebla Wenzel, 1966and Paradyschiria Speiser, 1900(Wenzel et al 1966Moura et al 2003). Paradyschiria fusca Speiser, 1900 and Noctiliostrebla aitkeni Wenzel, 1966 remains were found in 10% and 2% (respectively) of the feces of N. leporinus (Bordignon 2006).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Noctilio leporinus (Linnaeus, 1758) is often strongly infested by Noctiliostrebla Wenzel, 1966and Paradyschiria Speiser, 1900(Wenzel et al 1966Moura et al 2003). Paradyschiria fusca Speiser, 1900 and Noctiliostrebla aitkeni Wenzel, 1966 remains were found in 10% and 2% (respectively) of the feces of N. leporinus (Bordignon 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Noctilio leporinus and Myotis vivesi are primarily piscivorous (e.g. Blood and Clark, 1998;Bordignon, 2006), while several other species consume fish as an occasional dietary component (e.g. Fenton, 1990;Gudger, 1943;Law and Urquhart, 2000;Ma et al, 2003;Whitaker and Findley, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Although the zeugopodium/autopodium (zp/ap) length ratio of N. leporinus at the early juvenile B stage (0.92; Table ) is bigger than that reported for D. rotundus at the same developmental stage (0.74, revealing a bigger relative size of the autopodium at D. rotundus ), this relation is modified during the postnatal development to match the zp/ap ratios of both species at the early subadult F stage (1.29), finally exhibiting a bigger zp/ap ratio for D. rotundus (1.46) regarding N. leporinus (1.32; revealing a bigger relative size of the autopodium at N. leporinus ) at the adult H stage (Table ; Reyes‐Amaya et al, ). These developmental zp/ap ratios are associated with a bigger hindlimb autopodium (relative to the zeugopodium) at the fisher bat N. leporinus , which use the autopodium directly to acquire and handle the food (Bordignon, ; Brooke, ), in comparison with the common vampire bat D. rotundus , which use the autopodium during the terrestrial locomotion (Altenbach, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the calcar bone in bats serves as structural support for the edges of the uropatagium, facilitating the use of the uropatagium as a sac to capture and/or handle the food and as a rudder in manoeuvrability during flight (Schutt & Simmons, ; Stanchak & Santana, ; Vaughan, ). The presence of the calcar basal crest (Tables and ) at N. leporinus and N. albiventris suggests the high importance of the uropatagium–calcar complex (and associated muscles) in noctilionid fisher bats, related to the need to contract the uropatagium during the acquisition of the prey (avoiding the friction with the water, Vaughan, ) and its posterior use to handle the food (Bordignon, ; Brooke, ). The tibial lateral crest (extending along the lateral surface of the tibia, from one‐third way of the diaphysis length to its distal end; Figure c), which constitutes an increase in the origin/insertion surface for the m. extensor hallucis longus (rotation of the autopodium craniad and dorsad), m. gracilis (flexion of the shank and adduction of the hindlimb), m. semitendinosus and m. semimembranosus (extension of the femur and flexion of the shank, Vaughan, ). The presence of the tibial lateral crest at the zeugopodium of N. leporinus and N. albiventris (and hence the marked development of its associated muscles) is congruent with the great agility and strength of the hindlimb in noctilionid fisher bats, associated with the food acquisition and posterior handling during hunting (Bordignon, ; Brooke, ). The calcaneous dorsal slot (dorsal slot at the centre of the calcaneus; Figure a,b), which constitutes an increase in the origin surface for the m. flexor digitorum brevis (flexion of the digits, Vaughan, ). The proximal phalanges lateral slots (paired distal lateral slots at proximal phalanges I–V) and the proximal phalanges ventral slots (a ventral slot at epiphyses of proximal phalanges I–V; Figure f), which constitutes an increase in the insertion surface for the Mm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation